Основы электроснабжения: учебное пособие - Сивков А. А. Александр Анатольевич; Сайгаш А. С. Анастасия Сергеевна; Герасимов Д. Ю. Дмитрий Юрьевич (Томск, Изд-во ТПУ, 2014)
На обложке сост. указаны как авт.